Instrument Design and Performance for an L-BAND Reflector-Based SAR Mission - Younis, Marwan; Huber, Sigurd; Lopez-Dekker, Paco; Krieger, Gerhard (Advanced RF Sensors and Remote Sensing Instruments (ARSI) & Ka-band Earth Observation Radar Missions Workshop (KEO), 2014)
This paper provides an overview of the Tandem-L instrument design concept and its SAR performance predictions. Innovative aspects like the employment of advanced digital beamforming techniques and operation in a variety of imaging modes are detailed.
DLR Import::2019-04-03